Numerical investigation on the effect of building overhang on the flow within idealized two dimensional Street Canyon / Muhammad Fatih Ibrahim - Ibrahim, Muhammad Fatih (2022)
The purpose of overhang is to protect the pedestrian from a specific weather such as heavy rain and sunlight heat, which however conflicts with the previous studies on the effect of the overhang to the air quality within the canyon. Thus, the aim of this research his to investigate the influence of buildings overhang on the airflow and pollutant dispersion in the street canyon. The flow pattern and the pollutant concentration were evaluated by set up the overhang on the two types of typical building geometries namely flat roof and pitched roofs. This paper reported the results of the velocity flow field in a two-dimensional street canyon with different building overhang configuration using a computational fluid dynamics (CFD) by employing Reynolds Average Navier Stokes(RANS) approach. Simulation was conducted with a constant aspect ratio of W/H = 1,where W is the street width and H is the building height. A total of twelve cases of flat roof and pitched roof with no overhang, overhang on both sides, or overhang on either the leeward or windward side were simulated in order to get the understanding on the flow behaviour. The result shows that for the case of flat roof building, the pollutant concentration is higher on the windward side than on leeward side except for the case of 0.5HW as the counter-rotating vortex occur inside the canyon. On the contrary, the pollutant concentration is higher on the windward side for the case of pitched roof except for the case of pitched roof buildings with no overhang. The ratio of the canyon opening to the building height for some cases with a long overhang can be classified as a deep canyon and the flow regime are categorized as a skimming flow. Thus, in this study the case without overhang performs a better ventilation as the flow from the outer layer can penetrate well into the street canyon.